A Catalog of Prevention Strategies for Test Technical Debt - Silva, Levi Almeida; Santos, Ismayle Sousa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2024)
Background: The demand for software innovation pressures organizations to balance meeting deadlines with maintaining quality. This situation can lead to Technical Debt (TD), which refers to postponed development tasks that offer short-term gains but harm long-term quality. During the development process, the Testing phase also accumulates TD, known as Test Debt, which affects its effectiveness. Objective: To propose a strategy that supports preventive activities for Test Debts. Method: A literature review was conducted on Test Debts and their prevention strategies, establishing a relationship between these elements. Results: A catalog of 47 categories of strategies to prevent Test Debts was developed. Experts assessed the catalog and praised its clarity and usefulness in preventing Test Debts. Conclusion: The proposed catalog emerges as a tool that can assist professionals in decision-making to prevent the occurrence of Test Debts.